ChemInform Abstract: A Mild and Efficient CH2‐Extrusion Reaction for the Enantiospecific Synthesis of Highly Configurationally Stable Troeger Bases. Issue 43 (October 2015) - Pujari, Sandip A.; Besnard, Celine; Buergi, Thomas; Lacour, Jerome
Abstract Oxidation of ethano‐Troeger bases (I) and (III) with DDQ in wet nitromethane results in a highly enantiospecific methylene extrusion to afford ring contracted products (II) and (IV) which are significantly more configurationally stable than regular Troeger bases.